Efektivitas Blood Flow Restriction Exercise Dalam Peningkatan Quadricep Strength Pada Pasien Post Acl Rekonstruksi : Literature Review - Ginting, Auvin Joe (UI Scholars Hub, 2024)
This article aims to evaluate the Effectiveness of Blood Flow Restriction Exercise in Improving Quadriceps Strength in Patients with ACL Reconstruction. This project is a literature study in narrative form. The background for conducting this research is the high incidence of ACL tears, ranging from 78 to 81 cases per 100,000 population worldwide in a year. The most common surgical treatment provided is ACL reconstruction. Quadriceps strength reduction after 6 months post-operation reaches 20% compared to pre-operation. From the symptoms and clinical complaints of quadriceps muscle weakness, one of the interventions that can be performed is Blood Flow Restriction Exercise. A search was conducted using various databases, resulting in the discovery of 10 articles, which were then filtered and selected to obtain 7 articles. Rresulting in a final selection of 5 articles. The objective of this study is to determine the effectiveness, dosage, and success factors of BFRE in improving quadriceps muscle strength in patients post-ACL reconstruction using isokinetic and isometric dynamometers. Research results showed an increase in quadriceps muscle strength, even in knee function. The dosage provided varied but still had a positive impact. In conclusion, the administration of BFRE can be an intervention solution to improve quadriceps muscle strength in patients post-ACL reconstruction.